Postponement of Debt Payment Obligations as an Effort to Save Concurrent Creditors’ Rights to Debtors Engaged in Investment - Zulfikar, Muhamad (Devotion : Journal of Research and Community Service, 2023)
This study aims to analyze how legal protection for creditors who invest in companies engaged in investment, then the creditors experience losses due to the failure of the promised payment by the debtor within the specified time, so that the creditor files a PKPU application. This research was conducted using normative legal research methods. Based on the analysis of this problem, the PKPU process can be a solution to save the rights of concurrent creditors who have a very disadvantaged position if the debtor is declared bankrupt. Bankruptcy has the potential to be used as a shortcut for debtors to escape their obligation to pay debts. The existing regulations are also not enough to provide protection for concurrent creditors, especially for the existence of conditions of helplessness of concurrent creditors.